KiwiSaver: an evaluation of a new retirement savings scheme. Issue 3 (2nd September 2017) - Law, David; Meehan, Lisa; Scobie, Grant M.
ABSTRACT: This paper provides an evaluation of the performance of KiwiSaver, a subsidised voluntary savings scheme aimed at increasing the retirement wealth of a target population. Four key dimensions of performance are assessed using a variety of empirical techniques drawing on data from a national survey of 825 people conducted in 2010. Results suggest that only one-third of contributions to KiwiSaver represent additional savings. Regression analysis finds no relationship between KiwiSaver membership and expected retirement income outcomes. Examination of standard measures of programme efficacy such as target effectiveness and leakage suggests that KiwiSaver has been only modestly successful in reaching the target population and that leakage to the non-target population was high, at 93%. Finally, the scheme's possible effect on national saving was examined. In the long run, the effect on net national saving appears marginal at best.